PENGANTAR TEKNOLOGI INFORMASI UNTUK MENINGKATKAN PEMBELAJARAN SISWA DAN SISWI DI SEKOLAH DASAR NEGERI SEPATAN 2 - Indra Kristianto, S.Kom,. M.Kom; Meroni Gulo (Universitas Pamulang, 2025)
This community service program was carried out to address the low information technology literacy among students at Sekolah Dasar Negeri Sepatan 2, where access to basic computer education is limited. The objective was to introduce and build a fundamental understanding of information technology for fifth-grade students so they can use it wisely and productively. The method applied was an interactive approach through presentations, computer hardware demonstrations, and question-and-answer sessions with 89 participants. The results showed a significant improvement in students’ understanding of basic computer functions and awareness of both the positive and negative impacts of technology. Students became more enthusiastic and interested in using technology for learning, supported by positive feedback from the school. This program successfully enhanced students’ digital literacy and served as an effective initial step toward digital transformation in primary education. Keywords: Information technology, Elementary education, Digital literacy, Basic computer, Community service.